Pengaruh Media Sosial Terhadap Tingkat Pidana Narkotika di Sulawesi Tenggara - Mardiana Mardiana (Communicatus: Jurnal Ilmu komunikasi, 2018)
The problem in this study is how the influence of the use of social media as a communicative medium has an impacton the criminal level of narcotics use in Southeast Sulawesi region. The objective tobe a chieve disto find out how social media is able to improve the influence of narcotics distribution and transaction processes in Southeast Sulawesi. The location of this study was carried out in 3 cities in Southeast Sulawesi, namely Kendari, Muna and Kolaka Districts.The method used in the research data retrieval processis a quantitative method to provide an over view of the influence of social media onthe level of narcotics crime in Southeast Sulawesi. The data collection process is using a questionnaire with the number of respondents was 75 respondents. The results showed that there was a strong and significant influence of social media on the narcotics transaction process in the region of southeast Sulawesi, where the effect was indicated by the results of the regressi on test between social media variables X against criminal narcotics Y that is equal to 0.880 meaning that 88 %to of social media influence the level criminal narcotics in the Southeast Sulawesi region there maining 12 percent is influenced by other factors.Penelitian ini membahas bagaimana pengaruh penggunaan media sosial sebagai media komunikasi sehingga memberikan dampak terhadap tingkat pidana penggunaan narkotika di wilayah Sulawesi Tenggara. Tujuan yang ingin dicapai yaitu untuk mengetahui bagaimana media social mampumemberikanpengaruhterhadap proses penyebaran dan transaksi narkotika di Sulawesi Tenggara. Lokasi penelitian ini dilaksanakan di 3 kota yang ada di wilayah Sulawesi tenggara yaitu kota Kendari, Kabupaten Muna dan Kabupaten Kolaka. Adapun metode yang digunakan dalam proses pengambilan data penelitian yaitu metode kuantitatif untuk memberikan gambaran mengenai pengaruh media sosial terhadap tingkat pidana narkotika di Sulawesi tenggara. Proses pengumpulan datanya yaitu menggunakan kuesioner dengan jumlah responden sebanyak 75 responden. Hasil penelitian menunjukkan bahwa ada pengaruh yang kuat dan signifikan media sosial terhadap proses transaksi narkotika dalam wilayah Sulawesi tenggara dimana pengaruh tersebut ditunjukkan melalui hasil uji regresi antara variable media social X terhadap pidana narkotika Y yaitu sebesar 0,880 artinya sebesar 88 persen media social memberikan pengaruh terhadap tingkat pidana narkotika dalam wilayah Sulawesi tenggara sisanya sebesar 12 persen dipengaruhi oleh faktor lain.